2022
DOI: 10.1007/s10157-022-02180-6
|View full text |Cite
|
Sign up to set email alerts
|

Disease severity and renal outcomes of patients with chronic kidney disease infected with COVID-19

Abstract: Introduction While there is evidence of the presence of the coronavirus in the kidneys and resultant acute kidney injury (AKI), information on the effect of chronic kidney disease (CKD) on COVID-19 outcomes and its pathogenesis is currently lacking. Methods This retrospective, observational study evaluated the outcomes of all consecutive patients hospitalized during COVID-19 outbreaks in Meir Medical Center. Serum creatinine level was assessed before hospitalization (“b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
2
6
0
1
Order By: Relevance
“…Recently, Gur et al observed that despite comparable disease severity at presentation, COVID-19 patients with CKD had significantly more AKI events and required more renal replacement therapy during hospitalization than control COVID-19 patients did. Thus, the odds ratio for AKI was 5.8 (95%CI 3.8–8.7; p < 0.001) in CKD group vs. control group [ 28 ]. In a recent meta-analysis, Cai et al found that chronic kidney disease was an independent risk factor for developing AKI in hospitalized COVID-19 patients, i.e., OR = 4.56 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gur et al observed that despite comparable disease severity at presentation, COVID-19 patients with CKD had significantly more AKI events and required more renal replacement therapy during hospitalization than control COVID-19 patients did. Thus, the odds ratio for AKI was 5.8 (95%CI 3.8–8.7; p < 0.001) in CKD group vs. control group [ 28 ]. In a recent meta-analysis, Cai et al found that chronic kidney disease was an independent risk factor for developing AKI in hospitalized COVID-19 patients, i.e., OR = 4.56 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, chronic kidney disease (CKD) emerged as one of the strongest risk factors for severe COVID-19 [ 4 , 5 , 6 , 7 ]. Indeed, patients with advanced CKD are at an increased risk of mortality from several causes, led by cardiovascular disease (CVD) and infections [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…MHD patients are immunocompromised and may have other risk-factors associated with their primary renal disease, such as older age, diabetes, hypertension, etc. As such, they were found to be at increased risk for severe disease and mortality [ 16 , 17 , 18 , 19 ]. Therefore, with the release of the SARS-CoV-2 mRNA vaccine, MHD patients were prioritized for vaccination.…”
Section: Introductionmentioning
confidence: 99%